Planning Successful Museum Building Projects - Crimm, Walter L.; Morris, Martha; Wharton, Carole L. (Rowman & Littlefield Publishers, 2009)
In an era of expanded responsibility and constricted funding, museum personnel often need strong practical guidance on the best practices for building projects. The authors of Planning Successful Museum Building Projects discuss the reasons for undertaking building projects (new construction, renovation, expansion), the roles and responsibilities of key players, the importance of a strong vision, and the best methods for selecting architects and construction firms. They also offer in-depth information about budgeting and finance, feasibility studies, capital campaigns, marketing, and communications, as well as advice on how to live through the disorienting process of construction, manage post-opening needs, and evaluate the project's success over time. Planning Successful Museum Building Projects provides all the tools for successfully managing projects from predesign through opening and beyond.